ANALISIS DAYA SAING DAN STRATEGI PENGEMBANGAN AGRIBISNIS TEH INDONESIA - Nurunisa, Venty Fitriany; Baga, Lukman Mohammad (Forum Agribisnis, 2012)
In the last ten years, the performance of Indonesiaâs tea agribusiness has been decreased. It is shown by the decreasing of tea estate area by 2.18 percent per year, tea production decreased by 0.8 percent and export volume decreased by 1.07 percent per year. The Porterâs Diamond System analysis shows that the competitiveness of Indonesiaâs tea agribusiness is still weak. The main component of Indonesiaâs tea that supports each other are : 1) the resources factors with the domestic demand conditions, and also 2) the resources factors with the related and supporting industries. While in the supporting component, the government component only supports the resources factors component, and itâs clearly different with the chance component that supports all the main components. Finally, tea agribusiness development strategies in Indonesia was analyzed by using SWOT and Architecture Strategy, which were more directed to increase the performance of smallholders tea plantation by strengthening the role of farmer group and optimalizing the role of association. In the other hand, the strategies for government and private tea estate are more directed to increase the volume of production and product diversification which are important for improving the export oriented tea products. Other strategies that can be implied are 1) increasing the promotional activity and 2) spreading information about tea and its benefits to increase domestic tea consumption.